Legal Reconstruction of The Hexsa Helix Synergy and Collaboration Model Mainstreaming Child Rights (PUHA) In The Implementation of Child Friendly District/Cities Programs - Susanto, Fransiska Ayulistya; Purnamaningtyas, Anindita; Widagdo, Setyo; Arrsa, Ria Casmi (International Journal of Social and Local Economic Governance, 2022)
The Government's commitment to fulfilling and mainstreaming Children's Rights (PUHA) is carried out to realize the goals of national development, namely advancing general welfare and educating the nation's life as mandated by the fourth paragraph of the Preamble of the 1945 Constitution of the Republic of Indonesia which explicitly states that the State exists in order to protect all of Indonesia's bloodshed, promoting public welfare and educating the life of the nation. Furthermore, the commitment referred to is also based on the constitutional basis as set forth in the provisions of Article 28B paragraph (2), "Every child has the right to survival, growth and development and is entitled to protection from violence and discrimination. **)” and the provisions of Article 34 paragraph (1) which reads, “The state takes care of the poor and neglected children”. Therefore, a research was compiled with the theme of Legal Reconstruction of the Hexsa Helix Synergy and Collaborative Model of Mainstreaming of Children's Rights (PUHA) in the Implementation of Child-friendly District/City Programs. The formulation of the problems raised are (1) Why is a legal reconstruction of the Hexsa helix model of synergy and collaboration the Mainstreaming of Children's Rights (PUHA) needed in the implementation of the Child-Friendly District/City program? (2) What is the legal reconstruction model of the Hexsa helix synergy and collaboration model for Mainstreaming Children's Rights (PUHA) in the implementation of the Child-friendly District/City program as an alternative form of building a social inclusion strategy to achieve a more equitable development for fulfilling children's rights? The research method used is Normative Juridical with statutory approach and conceptual approach. While the literature used includes literature on children, the hexa helix concept, and child-friendly districts/cities. Further identification of legal materials is carried out on Primary Legal Materials which consist of a set of legal norms in the form of laws and regulations in the field of children's rights. Meanwhile, Secondary Legal Materials consist of libraries, journals, research findings, and KLA program performance reports stipulated by the Central Government and Regional Governments. For further analysis of legal material is carried out using the method of content analysis or content analysist to answer legal problems related to the idea of ??Legal Reconstruction of the Hexa helix Synergy and Collaborative Model of Mainstreaming Children's Rights (PUHA) in the Implementation of Child-Friendly Districts/Cities Programs